Pengaruh Inovasi Produk dan Kualitas Produk terhadap Keputusan Pembelian : Studi pada Produk Facetology - Esa Cahaya Purnomo; Devi Virgiana Hermansyah; Inda Arsyizil Quwwatin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to evaluate the impact of product innovation and product quality on consumer purchasing choices for local skincare products Facetology. The methodology used in this study is a quantitative approach and information collection is carried out through questionnaires to 104 Facetology product users in Bekasi City. The results of the analysis show that product innovation and product quality simultaneously have a positive and significant impact on purchasing decisions, both gradually and simultaneously. This is evidenced by the t-test, F-test, and Pearson correlation, which show that product innovation has a greater impact than product quality. The coefficient of determination (R²) value of 0.688 indicates that these two independent variables can explain 68.8% of the variation in purchasing decisions. This finding indicates that companies need to continue to innovate and maintain product quality so that consumer purchasing interest can increase.